Attribution of a record-breaking cold event in the historically warmest year of 2023 and assessing future risks - Yangbo Ye; Cheng Qian; Aiguo Dai; Yuting Zhang; Jiacheng Jiang; Xiaoye Zhang (npj Climate and Atmospheric Science)
Abstract An unexpected record-breaking cold event struck eastern China in December 2023, causing widespread transportation shutdowns, power supply shortages, and agricultural crop damage. The manner in which such an extraordinary cold event was formed under global warming is unclear, as is the way in which anthropogenic climate change may affect the present and future frequency and intensity of similar cold events. Here, we show that the large-scale atmospheric circulation associated with the warm Arctic was the main event driver, explaining 83 ± 2% of the intensity of the 2023 cold event, whereas the thermodynamic effect of climate change suppressed the event intensity by −6 ± 3% in ERA5 and −22 ± 2% in HadGEM3-A-N216. An attribution analysis based on coupled model simulations shows that, due to anthropogenic climate change, the frequency and intensity of 2023-like events decrease by 92.5 ± 2.5% and 1.9 ± 0.2 °C, respectively, under the 2023 climate state. The thermodynamic effect of anthropogenic climate change outweighs its dynamic effect. Future projections indicate that the frequency and intensity of these 2023-like events will further decrease by 95 ± 3% and 2.05 ± 0.25 °C by the end of this century under an intermediate-emissions scenario compared with estimates made under the present climate. In contrast, 2023-like events will be similar to present events when the 1.5 °C target of the Paris Agreement is achieved. These findings highlight the dampening effect of anthropogenic climate change on cold events, but adaptation measures for future risks of 2023-like cold events will be needed by the end of the century if carbon neutrality is achieved.